PENGARUH KOMPETENSI GURU DAN DISIPLIN KERJA TERHADAP KINERJA GURU DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING DI SMK SWASTA KOTA BEKASI - Arief Rachman; Achmad Fauzi; Sri Maulidia Permatasari; Amri Darwis (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
Abstract: The objective of this study was to evaluate the effect of competence and work discipline that can improve teachers performance with motivation as an intervening variable. In this study, dimensions were included as a limitation between variables. Data was processed using SmartPLS 3.0 which can also used to solve SEM problems. There were 350 teachers of private shchools in the city of Bekasi participated as respondents in this study. The results of this research show that: competence, work discipline had a positive and significant effect on motivation; competence, work discipline and motivation had a positive and significant effect on performance; the motivation variable as a mediation did not play a full role (partial mediation) in determining the direct relationship. Teachers should continuously develop their competencies in order to motivate and improve performance at work. Teachers with high motivation will promote their performance. This teachers need to increase motivation in the workplace in order to improve their performance.